Issues, concepts and structures in juvenile ski jumping - Haim, H. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Many nations try to find concepts and structures to find and educate young talents from beginners to world class athletes. They seek for appropriate training methods, create national competition systems, cooperate with other countries to organize international youth competitions and use the system of the International Ski Federation up to the annually performed World Championships for Juniors. Austria is the most successful nation in youth ski jumping with a simple structure from clubs to regional teams, education centers like "Schigymnasium Stams" and the national teams.